Rancang Bangun Aplikasi Keuangan Siswa Pada SMA Kemala Bhayangkari 3 Porong - Ndoili, Gustianita Detika; Sunarto, M.J Dewiyani; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
SMA Kemala Bhayangkari 3 Porong is the one of private Senior High School in the Porong Sidoarjo, under the auspices of Kemala Bhayangkari Ranting Pusdik Sabhara Porong Foundation. Found several obstacles to the process financial students in SMA Kemala Bhayangkari, among others as follows : 1) difficulty search financial information each students 2) many types of payment 3) the process of making the report took a lot of time 4) often happens a late payments. Based on the identification of the problems, so the solution offered is making financial application who be able to manage financial students, whether it is in the payment transaction, reports, charts, and information warning before it is due to of the parents. The results of the Final Task is the application financial of SMA Kemala Bhayangkari 3 Porong where the system made those can be presenting history payment each students, presents graphs and arrears acceptance of all types of payments in any grade, and can send a messages payment warning student before the due to of parents, so that it could prevent the occurrence of a late payments Keywords: Student Finance, Payments, SMA Kemala Bhayangkari 3 Porong